1965
DOI: 10.1139/v65-069
|View full text |Cite
|
Sign up to set email alerts
|

THE IONIZATION BEHAVIOR OF AMIDES IN CONCENTRATED SULFURIC ACIDS: II. APPLICATIONS OF THE HA FUNCTION TO RATES AND EQUILIBRIA

Abstract: ABSTRACT'The newly determined H. 4 scale of acidity has been tested against ionization ratio data for 33 amides. Twenty-nine of these compounds give log I vs. HA slopes of 0.9-1.1 and most are within 0.95-1.05. The average slope for these is 1.001 f 0.051. 'The H. 4 function is thus considered to be generally applicable to the ionization of this type of base, and the significance of previously reported amide p K values is discussed in the light of these results. Previously reported basicity-substituent constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1968
1968
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…This function was defined in the same way as the Hammett Ho function, but was based upon primary amides as indicators. Later they proved its validity for other amides (2). Earlier measurements of the basicity of amides indicated that most of them do not follow (3) the conventional acidity function Ho proposed by Hammett (4); these compounds are called "nonHammett" bases.…”
mentioning
confidence: 99%
“…This function was defined in the same way as the Hammett Ho function, but was based upon primary amides as indicators. Later they proved its validity for other amides (2). Earlier measurements of the basicity of amides indicated that most of them do not follow (3) the conventional acidity function Ho proposed by Hammett (4); these compounds are called "nonHammett" bases.…”
mentioning
confidence: 99%
“…They can be ignored for large but not for small values of R . Equations [I] and [2] apply to reactions or equilibria in solutions of zero ionic strength (13 (16). In these solutions the dielectric constant D, will be reduced (l8), and to a lesser extent D,,; this might account for the larger ApK (-2.7).…”
Section: ~T R~d ~~mentioning
confidence: 99%
“…In practice, it is found that slopes often vary from unity, but their closeness to unity is an indication of the applicability of the acidity function to the particular compounds. Values in the range 0.95-1.05 are desirable, but those between 0.9-1.1 are considered acceptable (11). Table 2 lists the 20 thiocarbonyl compounds investigated, along with the slopes of log I us.…”
Section: Applicability Of H Functionmentioning
confidence: 99%